KINERJA KARYAWAN DAN BAURAN PEMASARAN TERHADAP LOYALITAS NASABAH MELALUI KEPUASAN NASABAH SEBAGAI VARIABEL INTERVENING PADA BMT MBS CABANG KARAS - Rizka Dwi Anisa (Investama : Jurnal Ekonomi dan Bisnis, 2023)
Public enthusiasm for using service products or saving at BMT MBS Syariah is getting higher, as evidenced by the increasing number of customers and income increasing every year. But in fact there are some who quit and move to other institutions. This type of research is quantitative. Methods of data analysis using SmartPLS 3.0. The purpose of this study was to examine and analyze the effect of employee performance on customer loyalty and customer satisfaction, the effect of the marketing mix on customer loyalty and customer satisfaction, the effect of satisfaction on customer loyalty, the effect of employee performance on customer loyalty through customer satisfaction, the influence Marketing mix on customer loyalty through customer satisfaction. The results of this study are 4 hypotheses rejected and 3 hypotheses accepted. The hypothesis that was rejected was H1, namely employee performance has a positive effect on customer loyalty, H2, namely employee performance has a positive effect on customer satisfaction, H3, namely the marketing mix has a positive effect on customer satisfaction, and H6, namely employee performance on customer loyalty through customer satisfaction. While the accepted hypothesis is H4, namely the marketing mix has a positive effect on customer satisfaction, H5, namely customer satisfaction has a positive effect on customer loyalty and H7, namely the marketing mix on customer loyalty through customer satisfaction. The rejected hypothesis is an insignificant hypothesis because the t-statistic value is < 1.96 and the P value is > 0.05 (5%). Meanwhile, the accepted hypothesis is a significant hypothesis because the t-statistic value is > 1.96 and the P value is ≤ 0.05 (5%).